Implementation of the sensory organization test with the CAREN system: a pilot study - De Pasquale, Paolo; Ielo, Augusto; De Marchis, Cristiano; Borzelli, Daniele; Casile, Antonino; Caronni, Antonio; Scarano, Stefano; Calabrò, Rocco Salvatore; Tesio, Luigi; Quartarone, Angelo; d’Avella, Andrea (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe Sensory Organization Test (SOT) is a clinical and instrumental tool designed to assess postural stability by measuring body sway during standing under different sensory feedback conditions. This study explores the implementation of the SOT using the Computer Assisted Rehabilitation Environment (CAREN) system, aiming to enhance balance assessment and extend the diagnostic applications available for CAREN.MethodsA software application (CAREN-SOT) was developed to implement the SOT using the CAREN, which features a six degrees of freedom motion platform, force sensors, a 3D motion capture system, and an immersive visual environment. Eight healthy participants (ages 23–40, four males) underwent the SOT across six conditions, using either optic motion capture or force plate inputs to estimate the sway of the body center of mass. A generalized linear mixed model was employed to analyze equilibrium scores (ESs) from both modalities, considering system’s latency and responsiveness.ResultsCAREN-SOT implementation was possible using both input modalities. No statistically significant differences were found between the optoelectronic and force plate modalities in measuring postural stability across conditions. Comparison with normative data from the NeuroCom™ EquiTest™ system suggested equivalence in key SOT metrics, despite minor variations in ESs likely due to methodological differences and sample size.DiscussionBy integrating advanced technological and customization capabilities, CAREN-SOT provides an immersive, controlled environment for postural stability assessment. While findings must be validated on a larger sample, they support CAREN-SOT’s utility in diagnostic and rehabilitative settings. Future research directions include expanding normative datasets and exploring mediolateral sway to increase our understanding of postural control mechanisms.